543 Paroxysmal atrial fibrillation in a young athlete: the importance of knowing the electrophysiological mechanism. (8th December 2021) - Robles, Antonio Gianluca; Petrungaro, Mattia; Penco, Maria; Romano, Silvio; Sciarra, Luigi
Abstract: Aims: Atrial fibrillation (AF) is the most commonly sustained cardiac arrhythmia encountered in clinical practice. The prevalence of arrhythmia increases with age. However, paroxysmal AF can also arise in young or middle-aged individuals or otherwise healthy athletes. Electrical isolation of the pulmonary veins is the approach recommended by the guidelines for the ablative treatment of patients with symptomatic AF, although the risks associated with the procedure are not yet negligible. However, in order to increase the risk/benefit ratio of any ablation, it may be important to better define the electrophysiological mechanism underlying the arrhythmia. This could help plan a safer and more effective therapeutic approach, especially in young patients and/or patients with a structurally healthy heart and a prolonged history of paroxysmal AF. Methods and results: We report the case of a 19-year-old basketball player who is strongly symptomatic for palpitations due to AF episodes. The electrophysiological study revealed the true mechanism underlying AF episodes: degeneration into AF of an atrial tachycardia (AT) originating from the right atrium lateral wall. Once the ectopic focus of AT had been ablated, the patient remained totally asymptomatic at the 4-year follow-up. Conclusions: This case underlines the importance of the concept that young subjects with 'lone AF', in the absence of structural heart disease, may have different mechanisms underlying the arrhythmic phenomenon. In our case, the electrophysiological study enabled us to reconstruct the electrogenic mechanism at the base of the arrhythmia, allowing us to carry out a safe and effective therapy.